The skills of Polish emigrants Evidence from PIAAC - Brandt, Nicola (OECD Economics Department Working Papers, 2016)
Based on the OECD data from the Survey of Adult Skills (PIAAC) this paper sheds light on the skills of migrants. In line with earlier research the data show that migrants from Poland are more likely to have a tertiary degree than peers at home, but they often work in elementary professions abroad that do not match these high qualifications. This may well be at least partly a language issue, as migrants from Poland resemble migrants from other low-income countries in that their numeracy and literacy skills in the language of their host country is markedly lower than the average across all PIAAC participants, migrants or not. This gap is smaller, though, when looking only at migrants who report having been tested in a language that they use often and master well. The data reveal an interesting difference with migrants from higher-income countries, as their test results do not differ from the average, although they face the same language issues as other migrants. The reason may well be that only migrants from low-income countries can hope to earn higher wages abroad even if they work in low-skill professions, while migrants from higher-income countries need to master the language of their host country to do well. In fact, Polish migrants earn higher wages than their peers who stayed at home, even though they are particularly often overqualified